2019
DOI: 10.1002/jat.3824
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological safety assessment of the human‐identical milk oligosaccharide 3′‐sialyllactose sodium salt

Abstract: Human breastmilk is a mixture of nutrients, hormones and bioactive molecules that are vital for infant growth and development. Infant formula (IF) lacks many of these compounds, most notably human milk oligosaccharides (HMOs), which are abundant in breastmilk but scarce in IF. Sialyllactoses, such as 3′‐sialyllactose, constitute a large portion of the HMO fraction. To produce IF that matches breastmilk more closely, biosynthesized human‐identical milk oligosaccharides (structurally identical to HMOs) such as 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
(69 reference statements)
3
15
1
Order By: Relevance
“…Therefore, 5000 mg/kg BW/day (the highest dose tested) was established as the no-observed-adverse-effect level (NOAEL). This NOAEL corresponds to a total carbohydrate amount of 5220 mg/kg BW/day (accounting for 'other carbohydrates' in the 6′-SL preparation, see Table 1), which is consistent with previous observations for other HiMOs (Coulet et al, 2013;Coulet et al, 2014;Phipps, Baldwin, Lynch, Flaxmer, et al, 2018;Phipps, Baldwin, Lynch, Stannard, et al, 2018, Phipps et al, 2019.…”
Section: End Of Dosing Periodsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, 5000 mg/kg BW/day (the highest dose tested) was established as the no-observed-adverse-effect level (NOAEL). This NOAEL corresponds to a total carbohydrate amount of 5220 mg/kg BW/day (accounting for 'other carbohydrates' in the 6′-SL preparation, see Table 1), which is consistent with previous observations for other HiMOs (Coulet et al, 2013;Coulet et al, 2014;Phipps, Baldwin, Lynch, Flaxmer, et al, 2018;Phipps, Baldwin, Lynch, Stannard, et al, 2018, Phipps et al, 2019.…”
Section: End Of Dosing Periodsupporting
confidence: 90%
“…Thus, the absence of these findings in any of the recovery animals substantiates that they were not related to administration of 6′‐SL, as complete recovery of these testicular and epididymal findings would not be expected after only 4 weeks. There were also no test‐item‐related macroscopic or microscopic findings reported in another 90‐day toxicity study conducted with 6′‐SL (Gurung et al, ) nor in studies conducted with its constitutional (‘linkage's) isomer 3′‐SL (Kim, Gurung, Seo, Lee, & Woo, ; Phipps et al, , accepted manuscript), which further supports the conclusion that these findings were highly likely to be incidental and unrelated to the administration of 6′‐SL.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study, administration of HMO MIX 1 to neonatal farm piglets up to 8.0 g/L was not associated with any adverse outcomes. The lack of adverse effects in genotoxicity and sub-chronic studies conducted in rat with HMO Mix 1, 7 the safety of the individual oligosaccharides demonstrated with other safety studies, 8 19 and the results of this study support the safety of this ingredient in infant formulas, including those consumed during the sensitive period of human development below 12 weeks of age.…”
Section: Discussionsupporting
confidence: 76%
“…7 In these previous studies, HMO MIX 1 was demonstrated to be non-genotoxic and produced no adverse effects in animals at 10% of the diet, for a calculated dose of 5.67 g/kg and 6.97 g/kg in male and female rats, respectively. Other safety studies have been conducted on the individual HMOs in this novel mixture: 2′-FL, 8 10 3-FL, 11 LNT, 12 3′-SL, 13,14 and 6′-SL, 15,16 including previous studies in neonatal piglets for 2′-FL 17 and 3′-SL. 18,19 These previous studies and the long history of exposure via human milk at the concentrations intended to be added to infant formula strongly support the safety of these oligosaccharides to human infants.…”
Section: Introductionmentioning
confidence: 99%